Effects of sugar beet root based concentrates level on carcass characteristics and body components in Tagger male kids - Elimam, M. E; Elshafie, N. O. H.; Eltayeb, B. A; Ombabi, Y. A (Gezira Journal of Agricultural Science, 2017)
Twelve Tagger male kids at 6 month old were used to study the effects of dried sugar beet root (DSBR) based concentrates level on the performance and carcass characteristics in the Gezira State, Sudan. They were weighed, divided into 3 groups according to body weight (BW) and allocated at random to the 3 experimental diets. They were  housed in individual pens and weighed weekly before the morning meal for 8 weeks with a two weeks preliminary period. They were fed groundnut haulm (GNH) ad lib . in two equal meals at 8 am and 4 pm and different levels of DSBR based concentrates (0 (control), 150g and 300g) in two equal parts before GNH meals. The animals were slaughtered and body components and carcass characteristics were studied. Slaughter weight, hot carcass weight (9.62- 12.69 kg), EBW (7.39-10.1kg), dressing percentages (37.26-41.67), muscle (65.75-68.0%), fat (7.75-12.25%), muscle: bone (2.49:1- 3.58:1) and muscle: fat (8.79:1-10.6:1) increased and bone (26.50 -19.75%) decreased with concentrates level. Body components weight and percentages on live BW varied among and within concentrate levels and were mostly the heaviest in animals fed 300g concentrates. Body components weights and percentages were not significantly (P>0.05) affected by concentrates level, except kidneys and renal fat, mesentery and omentum. The highest percentages were higher in the control and least in animals fed 150g concentrates. It is recommended to use DSBR based concentrates in fattening Tagger kids.     استخدم 12 ذكر جديان من  التقر بعمر 6 أشهر لدراسة أثر مستويات عليقة مركزة تحتوي على جذور بنجر السكر الجافة على  صفات الذبيحة و مكونات الجسم الثانوية في ولاية الجزيرة بالسودان.  تم وزن الحيوانات وتقسيمها الى 3 مجموعات على أساس الوزن ووزعت عشوائيا على اعلاف الدراسة الثلاث. وضعت الحيوانات في حظائر فردية ووزنت أسبوعياً قبل وجبة الصباح لمدة 8 أسابيع منها أسبوعين فترة إعدادية.  أعلفت الحيوانات تبن الفول السوداني حسب الرغبة في وجبتين متساويتين عند الثامنة صباحا والرابعة مساء و مستويات مختلفة من عليقة مركزة ترتكز على جذور بنجر السكر الجافة  (صفر (الشاهد) 150و و300جم ( في جزئين قبل وجبات تبن الفول السوداني.  ذبحت الحيوانات وقيست مكونات الجسم الثانوية وصفات الذبيحة. أظهرت الدراسة ازدياد وزن الذبح والذبيحة الحارة(9.62- 12.69  كجم ) ووزن الجسم الفارغ (7.39-10.1  كجم) ونسبة التصافي (37.26 %– (%41. 67  علي أساس الوزن الحي و  42.875-52.15%  علي أساس الوزن الفارغ ونسب العضلات (65.75  %- 68.00%) والدهون (7.75%-12.25%) ونسبة العضلات للعظام ( %2.49- %3.58 ) والعضلات للدهون 8.79%-10.6 (% و تقل نسب العظام (19.75%-26.50% (مع زيادة مستوي العليقة المركزة بدون فروق معنوية .  تباينت أوزان مكونات الجسم الثانوية ونسبها على أساس وزن الجسم بين وداخل مستويات العليقة المركزة وكانت أعلي في الحيوانات المغذاة علي 300 جم عليقة مركزة وأقلها في  مجموعة الشاهد . لم تكن الفروقات في أوزان ونسب مكونات الجسم الثانوية معنوية عدا الكلي ودهنها والمساريقا ودهن الأحشاء. كان عدد النسب المئوية الأعلى أكبر في مجموعة الشاهد واقل في التي أعلفت 150 جم عليقة مركزة. يوصي باستخدام علائق تحتوي على  جذور بنجر السكر الجافة لتسمين جديان ماعز التقر